Mapping the Relationship Between Green Innovation and Financial Performance: A Bibliometric Analysis - Kasriani, Kasriani; Wahyuni, Ersa Tri; Rosdini, Dini (E-Jurnal Akuntansi, 2024)
This research emerged due to the increasing issue of a company’s sustainable development, especially the environment that affects financial performance. Finding, characterizing, and analyzing the evolution of research publishing trends investigated by researchers globally is the goal of this systematic literature review model study. Using the SR technique as the central methodology, researchers gathered 138 documents from the Scopus database between 2013 and 2023. The findings indicate that the number of publications from joint studies of different nations worldwide has significantly increased. These papers include topics such as the impacts of GI and the urgency of implementing it. Access to study data, funding assistance, and researcher interest all affect the annual rise. This study offers several recommendations to improve organizational knowledge related to GI and FP.